Diurnal variations of plankton diversity and physico-chemical characteristics of Rewalsar Wetland, Himachal Pradesh, India - Jindal, R; Thakur, R K (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> The contemporary examination signifies diurnal variations in various physico-chemical parameters of Rewalsar wetland during summer and winter. Fluctuations in the intensity and duration of solar radiations, temperature, photosynthesis, respiration and decomposition were the major factor responsible for diel fluctuations in the physico-chemical factors. Water temperature showed increment from 24.82°C to 29.20°C in June and from 9.15°C to 12.95°C in January. Minimum and maximum values of temperature were recorded at 06.30 hrs and 14.30 hrs respectively. Secchi disc transparency was low in the wetland due to abundance of phytoplankton. It ranged from 0.00-121.00 cm during summer and 0.00-131.00 cm during winter. Oxygen percentage saturation values were minimum (summer 26% and in winter 58%) in the morning at 06.30 hrs and reached maximum (70% in summer and 100% in winter) in the afternoon at 14.30 hrs. Free carbon dioxide was present only at 06.30 a.m. in winter. The pH of water remained alkaline and increased from 10.30 hrs to 14.30 hrs, thereafter it decreased again. Carbonates were present only in January (0.00-5.80 mg L–1). Bicarbonates were 132.52-152.50 mg L–1 in June and 92.35-121.23 mg L–1 in January. The values for chloride, hardness and electrical conductance were higher during summer as compared to winter. Total hardness showed fluctuations from 163.45 to 181.24 mg L–1 in summer and 121.45 to 140.72 mg L–1 in winter, chloride. Phytoplankton were composed of members of Bacillariophyceae, Chlorophyceae, Cyanophyceae, Euglenophyceae and Cryptophyceae. Phytoplankton showed up movements during day time and down movement after sunset. Zooplankton were composed of Rotifera, Cladocera and Copepoda. They showed up migration during night hours and down migration during day.